A preliminary investigation on water quality of water courses in oil palm smallholdings converted from peat swamp and mangrove forests - Abd. Rahman, Mohd Afendy; Abu Bakar, Siti Nurhidayu; Md Sharif, Badrul Azhar; Sulai, Petra; Shamsuddin, Siti Aisah (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Oil palm smallholdings had been extensively established at the expense of peat swamp or mangrove forests. This study was conducted at peat swamp forest converted (PF) and mangrove forest-converted (MF) sites in Tanjung Karang, Selangor. Dissolved oxygen (DO), pH, temperature, electric conductivity (EC), turbidity, salinity and total dissolved solids (TDS) were measured with corresponding water levels at 25 stations in each study site. Kruskal-Wallis Analysis of Variance was used to compare the means of each water quality parameter for both study sites while the Spearman’s correlation tests were used to detect any collinearity between parameters. The preliminary results indicated that EC, salinity, pH and TDS were significantly higher in MF compared to PF (Kruskal Wallis p < 0.001) due to the high salt concentration in MF and low pH in PF. Although both study sites were converted to oil palm about 50 years ago, the water quality measured suggest that the levels were much influenced by the original land cover.